Thailand : Why Liberalization May Stall in a Mature Power Market - World Bank (Washington, DC, 2014)
This review argues that, following the 1997 crisis, the proposed reform plan was helped by some particularly conducive country factors: a tough, but not paralyzing challenge, a quick return to macroeconomic stability, and, and influential reform champion. However, many sector factors worked against the plan, among these were the sector's acceptable level of efficiency, and consistent resistance by incumbent state-owned utilities, and a biased reading of the international experience. Although market liberalization was politically feasible, its political desirability was weak. The report pays particular attention to: 1) sequencing reform; 2) adapting and making amends to the market model, but minimizing risks, and cost of market failures in a developing country context; and, 3) selling the reform, by improving perceptions of benefits and costs, especially mitigating social impacts. Particularly suggested is the interaction between the political economy, and the technical design of reform, i.e., in order for negotiations to arrive at a politically desirable, and feasible roadmap, they must be subjected to a technical scrutiny, that ensures that the final reform plan is sound.